Giesbertiolus curoei, a new species of flower chafer from Panama with transitional characters (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini) - Ramírez-Ponce, Andrés (Zootaxa, 2014)
Giesbertiolus curoei, new species is described from a female specimen collected in northwestern Panama. This species is compared with the three known species of Giesbertiolus Howden and with the genus Dialithus Parry. The genera Dialithus and Giesbertiolus are redefined to include this new species, and new diagnostic characters are provided for both. Illustrations of diagnostic characters and an identification key for the species of Giesbertiolus are provided.